Brain regional pharmacokinetics following the oral administration of curcumagalactomannosides and its relation to cognitive function. (2nd September 2022) - Kannan, Ramalingam G.; Abhilash, Maliakal B.; Dinesh, Kumar; Syam, Das S.; Balu, Maliakel; Sibi, Ittiyavirah; Krishnakumar, I. M.
ABSTRACT: Objective: Though a number of bioavailable formulations of curcuminoids have been reported and available commercially as nutraceuticals for brain health, systematic informations on their blood–brain-barrier permeability and brain tissue distribution have not been reported. The present study was aimed to investigate the brain regional pharmacokinetics of curcuminoids following both single dose and repeated dose oral administration of a self-emulsifying food-grade formulation of curcuminoids using fenugreek galactomannan hydrogel scaffold as 'curcumagalactomannosides' (CGM), and its influence on cognitive functions in comparison with unformulated natural curcuminoids (NC) in Wistar rats. Methods: CGM was given to animals in single dose (100 mg curcuminoids/kg b. wt.) and repeated dose (100 mg curcuminoids/kg b. wt. for 28 days) and the concentration of total curcuminoids at various parts of brain was evaluated at different time points using Ultra-performance liquid chromatography/electrospray ionization triple quadruple tandem mass spectroscopy (UPLC-ESI-MS/MS) system. Another set of animals were also fed with CGM at single dose (100 mg curcuminoids/kg b. wt.) and repeated dose (100 mg curcuminoids/kg b. wt. for 28 days) and the behavioural studies were conducted using open field test and radial arm maze. Results: UPLC-ESI-MS/MS analyses of plasma revealed significant absorption of unconjugated (free) curcuminoids upon both single and repeated dose administration of CGM with maximum concentrations of 173.34 ± 27.12 ng/mL and 223.22 ± 32.73 ng/mL, respectively. Further analysis of brain tissues demonstrated significant blood–brain-barrier permeability. Brain regional pharmacokinetics (AUC, C max and t 1/2 ) indicated a relative distribution order of hippocampus > striatum > cerebellum > cerebral cortex > brain stem. Supplementation of CGM for 28 days also offered significant ( p   <  0.05) improvement in locomotor activity and reduction in spatial memory errors as compared to NC. The NC treatment also improved the behaviour better than the vehicle-treated group. Conclusion: CGM could distribute significant amount of free curcuminoids, in brain especially in the hippocampus at both single and repeated dose administration with an elimination half-life of 2.6 h. CGM also showed a positive impact in behaviour of animals in comparison with normal unformulated curcuminoids.